2006
DOI: 10.1073/pnas.0607313103
|View full text |Cite
|
Sign up to set email alerts
|

Coactivator as a target gene specificity determinant for histone H3 lysine 4 methyltransferases

Abstract: Activating signal cointegrator-2 (ASC-2), a coactivator of multiple transcription factors that include retinoic acid receptor (RAR), associates with histone H3-K4 methyltranferases (H3K4MTs) MLL3 and MLL4 in mixed-lineage leukemia. Here, we show that mice expressing a SET domain mutant of MLL3 share phenotypes with isogenic ASC2 ؉/؊ mice and that expression and H3-K4 trimethylation of RAR target gene RAR-␤2 are impaired in ASC-2-null mouse embryo fibroblasts (MEFs) or in MEFs expressing siRNAs against both MLL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
231
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(247 citation statements)
references
References 39 publications
14
231
2
Order By: Relevance
“…Importantly, ASC-2 is an integral and unique component of a Set1-like complex named ASCOM (for ASC-2 complex), which contains MLL3 or MLL4 (5,10). ASCOM indeed possesses H3K4MT activity (5,(10)(11)(12). More recent studies identified additional components of ASCOM, including UTX (11,12), a protein subsequently shown to be a H3K27-demethyase enzyme (13)(14)(15)(16).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, ASC-2 is an integral and unique component of a Set1-like complex named ASCOM (for ASC-2 complex), which contains MLL3 or MLL4 (5,10). ASCOM indeed possesses H3K4MT activity (5,(10)(11)(12). More recent studies identified additional components of ASCOM, including UTX (11,12), a protein subsequently shown to be a H3K27-demethyase enzyme (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…In these mice, WT MLL3 is replaced by a mutant MLL3 that bears an in-frame deletion of a 61-aa catalytic core region in the MLL3 SET domain and is expressed and incorporated into ASCOM (10). Unlike ASC-2-null mice, which die at approximately embryonic day (E) 9.5-E13.5 (19)(20)(21)25), MLL3 ⌬/⌬ mice in C57BL/ 6-129S6 background show only a partial embryonic lethality (10).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MLL proteins possess methyltransferase activity specifically directed at lysine 4 of histone H3 (H3K4), and especially trimethylation of this residue (H3K4me3) (Ruthenburg et al, 2007). Menin is part of the MLL1 and MLL2, but not of the MLL3 or MLL4 complexes (Lee et al, 2006). The menin-MLL1 histone methyltransferase (HMT) complex was found to be important for -catenin regulated transcription of the c-Myc gene and is stabilised by the chromatin-associated protein lens epithelium-derived growth factor (LEDGF) (Sierra et al, 2006, Yokoyama andCleary, 2008).…”
Section: Introductionmentioning
confidence: 99%